2015
DOI: 10.1038/nature15247
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the mammalian mechanosensitive Piezo1 channel

Abstract: Piezo proteins are evolutionarily conserved and functionally diverse mechanosensitive cation channels. However, the overall structural architecture and gating mechanisms of Piezo channels have remained unknown. Here we determine the cryo-electron microscopy structure of the full-length (2,547 amino acids) mouse Piezo1 (Piezo1) at a resolution of 4.8 Å. Piezo1 forms a trimeric propeller-like structure (about 900 kilodalton), with the extracellular domains resembling three distal blades and a central cap. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
450
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 385 publications
(489 citation statements)
references
References 75 publications
22
450
1
Order By: Relevance
“…This protein has been identified in the RBC membrane, and in mice it has been shown to form a tetramer of about 1.2 million daltons; it is therefore the largest ion channel identified to date, and moreover it regulates mechanotransductive release of ATP from human RBCs. [40][41][42][43] The identified mutations are missense and mainly located in the highly conserved C-terminus of the protein, recently described to form the pore of the channel. 44 Several electrophysiology studies demonstrated that the mutations cause a gain-of-function phenotype with delayed inactivation of the channel, 38,39,45 sugUpdate of the red cell membrane disorders haematologica | 2016; 101 (11)gesting increased cation permeability leads to DHS erythrocyte dehydration.…”
Section: Anemias Due To Altered Permeability Of Rbc Membranementioning
confidence: 99%
“…This protein has been identified in the RBC membrane, and in mice it has been shown to form a tetramer of about 1.2 million daltons; it is therefore the largest ion channel identified to date, and moreover it regulates mechanotransductive release of ATP from human RBCs. [40][41][42][43] The identified mutations are missense and mainly located in the highly conserved C-terminus of the protein, recently described to form the pore of the channel. 44 Several electrophysiology studies demonstrated that the mutations cause a gain-of-function phenotype with delayed inactivation of the channel, 38,39,45 sugUpdate of the red cell membrane disorders haematologica | 2016; 101 (11)gesting increased cation permeability leads to DHS erythrocyte dehydration.…”
Section: Anemias Due To Altered Permeability Of Rbc Membranementioning
confidence: 99%
“…For instance, the peripheral regions may function as force sensors and transducers to gate the central pore. In line with this idea, comparing the different classes of cryo-EM structures of Piezo1 reveals that the peripheral regions, particularly the 'blade' domains, are highly flexible [6].…”
mentioning
confidence: 70%
“…They first reported in Nature a cryo-electron microscopy (cryo-EM) structure of the full-length mouse Piezo1 protein (2547 residues per monomer), revealing its overall architecture and distinct domains [6]. In another study published recently in Neuron, on the basis of the Piezo1 structure they carried out a comprehensive structure-guided functional analysis, leading to the identification of the ion-conducting pore and key pore determinants, as well as mechanotransduction components, which define the ion-conducting properties and gating by mechanical stimuli, respectively [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations